Cryopreservation of engineered tissues - Modelling of the transport of cryoprotecting agents - Cui, Z; Xu, X; Urban, J; Sambanis, A; Nerem, R (2002)
Mathematical models to describe the diffusion of single cryoprotecting agents (CPA) and multiple CPAs in tissue contructs were developed. Fick's law was used to describe single CPA diffusion, and Maxwell-Stefan approach was used to describe multiple CPA transport inside the tissue. The model used to to stimulate the CPA loading in articular cartilage and blood vessel constructs. Experimental work using diffusion chambers was carried out to determine the model parameters and verify the models.